El impacto de las microfinanzas como herramienta de desarrollo económico en la provincia de Loja - l Espinosa Armijos, Edwin Joel (2024)
Microfinance has experienced significant growth in developing countries, especially in rural areas with limited access to financial services. Microfinance is aimed primarily at low- income people and businesses that do not have access to traditional financial services. This sector focuses on providing financial services, such as small loans, savings accounts and insurance, to individuals and communities in vulnerable economic situations, mainly in rural areas. Therefore, the objective of the study is to identify how microfinance contributes to economic development in the province of Loja. For this purpose, a quantitative approach was used, analyzing the relationships between financial indicators such as microcredit volumes, amounts and operations of public and private banking institutions and the popular and solidarity economy (EPS), as well as domestic consumption and population density. The data used in this study correspond to the 2015 2020 period. The results show that financial institutions in the EPS sector have a positive and significant impact on economic development, thanks to their inclusive and personalized approach, which allows users to better face their challenges. It is therefore concluded that both microfinance products and services drive the creation and growth of small businesses, generating employment and increasing incomes in disadvantaged communities.